Microbiological Assessment of Sliced Carica papaya (Pawpaw) and Citrullus lanatus (Watermelon) Sold in Lafia Metropolis - Angbalaga, Gladys Abel; Akeh, Martins Agianpuye; Anzene, Ablaku Asso (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
Fresh fruits are essential components of a healthy diet due to their high content of vitamins, minerals, and antioxidants. Among these, Carica papaya (pawpaw) and Citrullus lanatus (watermelon) are particularly valued for their nutritional benefits. This study assessed the microbiological contamination of sliced pawpaw and watermelon sold in Lafia Metropolis using standard microbiological procedures. For Carica papaya, total bacterial counts (TBC) ranged from 3.4 × 10⁴ to 3.8 × 10⁴ CFU/g, while total fungal counts (TFC) ranged from 1.9 × 10³ to 2.3 × 10³ CFU/g. For Citrullus lanatus, the TBC ranged from 4.0 × 10⁴ to 4.4 × 10⁴ CFU/g, and the TFC from 2.9 × 10³ to 3.2 × 10³ CFU/g. A statistically significant association was observed across the variables for both fruits among the selected locations (p < 0.001). The bacterial isolates from Carica papaya included Staphylococcus aureus, Escherichia coli, Salmonella spp., Pseudomonas aeruginosa, and Bacillus cereus, while fungal isolates included Aspergillus niger, Penicillium spp., Candida spp., Fusarium spp., and Rhizopus stolonifer. The bacterial profile of Citrullus lanatus was similar, except that Listeria monocytogenes was also isolated; fungal isolates were identical to those from Carica papaya. These findings highlight the need for stringent hygiene practices during the handling and sale of sliced fruits in Lafia Metropolis to safeguard public health. It is recommended that food regulatory bodies create awareness and educate the public on the health risks associated with consuming such contaminated fruits.